Brain injury in boxers and soccer players; an advisory report from the National Health Council of the Netherlands - de Bruijn, S.; Keunen, R. W. (Nederlands Tijdschrift voor Geneeskunde, 2004)
The National Health Council of the Netherlands has released a report entitled 'Brain damage in boxers and soccer players'. It examines epidemiology and prevention of cerebral damage from professional and amateur sports, focusing particularly on soccer and boxing. The connection between cerebral injuries and acute and chronic sports injuries is well established. However, proper diagnosis and therapy may be difficult in acute head trauma and during the chronic stage. It makes proposals for a simple cognitive screening test for acute injuries (soccer-related in particular) and more extensive testing for the detection and follow-up of chronic cerebral injuries (boxing-related in particular). Neuropsychological testing may be an important additional diagnostic tool. Professional boxing should be banned if the measures suggested fail to prevent chronic cognitive dysfunction. A dedicated knowledge centre for soccer and boxing would enhance the epidemiology and knowledge of brain injuries, and could help to develop more evidence-based guidelines in the future.